Comparison of Tuberculosis Infection Control Programs in Canadian Hospitals Categorized by Size and Risk of Exposure to Tuberculosis Patients, 1989 to 1993 – Part 2 - Donna Holton; Shirley Paton; Helen Gibson; Geoffrey Taylor; Carol Whyman; TC Yang (Canadian Journal of Infectious Diseases)
OBJECTIVE: To analyze tuberculosis (TB) programs in acute care hospitals (hospitals) categorized by size and risk of exposure to TB patients from 1989 to 1993.